Pembuatan dan Karakterisasi Teh Herbal Penurun Gula Darah dari Buah Mahkota Dewa dan Bunga Telang - Zakki Rosmi Mubarok; Nur Rohmah; Nurul Istiqomah Kusmuldayinah (Jurnal Ilmiah Teknik Kimia, 2022)
This study was conducted to compare the saponin contents and understand the characterization of herbal teas from the Mahkota Dewa fruit and the Telang flower for reducing blood glucose. The method of processing the of the Mahkota Dewa fruit and the flower of the telang into herbal teas is by gradually drying in the oven at a temperature of 110°C for 30 minutes and 70°C for 1 hour, then did size reduction and put into tea bags weighing 2.5 g per bag for 100 ml of water. The results showed that Mahkota Dewa tea had a higher saponin content of 14.4% and a water content of 6.5% more than the Telang flower with a saponin content of 5.6% and a moisture content of 5%. The results of the hedonic test analysis with  ANOVA showed that there was a significant difference between the two herbal teas in terms of color but there was no significant difference in terms of taste and aroma. In general, the Mahkota Dewa fruit tea and Telang flower tea were accepted by the panelists on a scale of 3-5 (neutral-very like). For 7 days, the pH of the steeping of Mahkota Dewa tea and Telang flower tea increased from pH 6 to 9. The results of the life test of Mahkota Dewa fruit tea and Telang flower tea can be kept for three days at cold temperatures (10°C–4°C) and one day for room temperature (20°C-25 °C).